Bacteria Analysis in the Ciwalen River Garut using Next Generation Sequencing of 16S Ribosomal RNA - Tati Kristianti; Lida Amalia (Berkala Ilmiah Biologi, 2023)
The Ciwalen River flows through Garut, which is bordered by hundreds of leather tanning enterprises and community toilet waste. The purpose of this research is to analysis bacteria in Ciwalen river water using the Next Generation Sequencing (NGS) method of the 16s ribosomal RNA gene. The primers utilized are the V1-V9 primers for the 16s rRNA sequence, which will amplify the entire length of the rRNA gene and allow for species identification. The data revealed that there were 104,000 reads, 150,232,539 bases, and 81,761 bacterial species. Proteiniclasticum ruminis, Fusibacter ferrireducens, Fusibacter fontis, Fusibacter tunisiensis, Paludibacter propionicigenes, Arcobacter cloacae, Alishewanella jeotgali, Thiovirga sulfuroxydans, Pseudomonas fluvialis, and Thauera mechernichensis are the main bacterial species. In this study, another bacteria, Klebsiella pneumoniae, was also found which is known to degrade heavy metals, Cr, Pb and Cd. The profile of bacteria, as well as the presentation of their existence in this water sample, demonstrates the appropriateness of heavy metals from leather tannery waste in the Ciwalen river.